Efektivitas Media Board Game Monopoly Terhadap Hasil Belajar Siswa Sekolah Dasar pada Materi Salat Rawatib - Resfita, Devi; Yulianengsih, Neng Lia (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Low student learning outcomes in the Islamic Religious Education (PAI) subject indicate a need for more innovative and interactive learning media. This study aims to determine the differences and improvements in student learning outcomes before and after using a Monopoly-style board game as a learning medium for the topic "The Joy of Rawatib Prayers." The study employed a quantitative approach using a pre-experimental method and a one-group pretest-posttest design. The subjects consisted of 16 third-grade students from SDN 1 Sukarapih. Data were collected through tests, observation, and documentation, then analyzed using the Shapiro-Wilk normality test, the Wilcoxon Signed-Rank Test, and N-Gain analysis with the aid of IBM SPSS Statistics 26. The results indicate a significant difference in learning outcomes before and after using the Monopoly board game, with an Asymp. Sig. (2-tailed) value of 0.000 (p < 0.05). Average learning outcomes also improved, with an N-Gain value of 0.4140, falling into the medium category. Thus, the use of the Monopoly board game is associated with improved student learning outcomes regarding the topic of Rawatib prayers and can serve as an alternative PAI learning medium in elementary schools.